Comparative Study Between Chicken Gizzards and Beef as Diets and its Influences on the Post-Embryonic Development and Longevity of Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) - Lourinho Dallavecchia, Daniele; Pedroso Ferraz, Adriana Cristina; Silva de Miranda, Gustavo; Sousa da Silva, Alexandre; Magalhães-de-Aguiar, Valéria (EntomoBrasilis, 2015)
Chicken gizzard was tested as an alternative to beef diet for creating Chrysomya megacephala (Fabricius) to reduce costs and optimize the time of diet preparation and maintenance of the colony diet. Forty newly hatched larvae were placed in 100 grams of diet: gizzard and meat (control). The experiment was performed in triplicate. The mass of mature larvae was recorded in semi-analytical balance and separate batch of five. After emergence, three replicates of 10 pairs of adults were formed. The post-embryonic development was evaluated by Tukey’s test at a 5% level of significance and longevity was adjusted Weibull regression. The mass of mature larvae showed no significant difference. The larval stage of flies reared in meat was longer. Pupae and newly emerged adults showed no significant differences as a function of diet. The increased mortality rate after after 22 days in both experimental diets. Greater longevity was achieved with diet gizzard, which was more efficient than the meat on the biological parameters studied. Estudo Comparativo entre a Moela de Frango e Carne Bovina como Dietas e suas Influências sobre o Desenvolvimento Pós-Embrionário e Longevidade de Chrysomya megacephala (Fabricius) (Diptera: Calliphoridae) Resumo. Moela de Frango foi testada como dieta alternativa à carne para criação de Chrysomya megacephala (Fabricius) visando reduzir custos e otimizar o tempo de preparação da dieta e manutenção da colônia. Quarenta larvas recém eclodidas foram colocadas em 100 gramas de dieta: moela e carne (controle). O experimento foi realizado em triplicata. A massa das lavas maduras foi registrada em balança semi-analítica e separada em lotes de cinco. Após a emergência, foram formadas três repetições de 10 pares de insetos adultos. O Desenvolvimento pós-embrionário foi avaliado pelo teste Tukey com nível a 5% de significância e a longevidade foi ajustada por regressão Weibull. A massa das lavas maduras não apresentou diferença significativa. A fase larval de moscas criadas em carne foi mais longa. Pupa e adultos recém-emergidos não apresentaram diferenças significativas em função da dieta. A mortalidade aumentou após 22 dias de experimento em ambas as dietas. Uma maior longevidade foi conseguida com a dieta moela, que se mostrou mais eficiente do que a carne sobre os parâmetros biológicos estudados.